Congenital Anomalies of Kidney and Urinary Tract in a Dissected Cadaver: Case Report - Mohammad Hassan Sakhaie; Marziyeh Pooladi; Soheila Madadi; Yusef Abbasi (Journal of Mazandaran University of Medical Sciences, 2023)
Congenital anomalies of the kidneys and urinary tract account for about 30% of malformations diagnosed in children. These malformations may have derived from cellular and molecular deterioration. Some of these abnormalities, including accessory renal arteries, ureter duplication, and lobulated kidneys require early diagnosis before kidney transplantation and pelvic surgeries. During the routine dissection of an about 60-year-old man cadaver at Arak University of Medical Sciences, some congenital anomalies of the urinary system, including bilateral ureter on the left side and lobulated of both kidneys were observed. In this case, also an accessory renal artery was originated from the abdominal aorta and entered the lower pole of the left kidney hilum. Immediate identification of accessory renal arteries and duplicated ureters are necessary for kidney transplantation and prevention of vesicoureteral reflux. Early diagnosis of these problems through clinical symptoms and radiographic images before surgery is important as it reduces the possibility of errors or surgery compilations.